2010
DOI: 10.1177/1074248409356063
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Flow and Function in Hypertension: Protective Effects of Pycnogenol in Hypertensive Participants—A Controlled Study

Abstract: This study evaluated the effects of Pycnogenol as an adjunct to angiotensin-converting enzyme (ACE)-inhibitor ramipril treatment of hypertensive patients presenting with early signs of renal function problems. One group of 26 patients was medicated with 10 mg ramipril per day only; a second group of 29 patients took Pycnogenol in addition to the ACE inhibitor over a period of 6 months. At trial end, a lowered systolic and diastolic blood pressure was found in both groups, with a significant further reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…The improvement of endothelial function with Pycnogenol was shown to decrease blood pressure in individuals with essential hypertension (Hosseini et al ., ; Zibadi et al ., ). These effects have been attributed to vaso‐dilatation which is associated with an improved level of perfusion as previously shown in peripheral circulation, the retina and the kidneys (Cesarone et al ., ; Steigerwalt et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The improvement of endothelial function with Pycnogenol was shown to decrease blood pressure in individuals with essential hypertension (Hosseini et al ., ; Zibadi et al ., ). These effects have been attributed to vaso‐dilatation which is associated with an improved level of perfusion as previously shown in peripheral circulation, the retina and the kidneys (Cesarone et al ., ; Steigerwalt et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The improvement of endothelial function with Pycnogenol was shown to decrease blood pressure in individuals with essential hypertension (Hosseini et al, 2001, Zibadi et al, 2008. These effects have been attributed to vasodilatation, which is associated with an improved level of perfusion as previously shown in peripheral circulation, the retina, and the kidneys (Cesarone et al, 2008a, Steigerwalt et al, 2009. In individuals with metabolic syndrome, elevated blood pressure and blood glucose are the main factors related to the development of renal dysfunction presenting as micro-albuminuria (Atkins et al, 2003).…”
Section: Introductionmentioning
confidence: 82%
“…White blood cell and red blood cells counts and clotting factor remained within the normal range. Subjects were interviewed for adverse effect, but none was reported by any of the subject (Cesarone et al , , ).…”
Section: Clinical Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Diastolic BP fell from 93.8 mmHg to 92.0 mmHg. Pycnogenol acts as a natural ACEI, protects cell membranes from oxidative stress, increases NO and improves endothelial function, reduces serum thromboxane concentrations, decreases myelo-peroxidase activity, improves renal cortical blood flow, reduces urinary albumin excretion and decreases HS-CRP [243][244][245][246][247] . Other studies have shown reductions in BP and a decreased need for ACEI and CCB, reductions in endothelin-1, HgA1C, fasting glucose, LDL-C and myeloperoxidase [244,245,247] .…”
Section: Pycnogenolmentioning
confidence: 99%